SYNCRETISM OF PUBLIC MYTHOLOGICAL CONSCIOUSNESS OF ANCIENT PORES - Kairzhanov, Abay K.; Kamzabekuly, Dikhan; Ilyassova, Zibagul; Azmukhanova, Aiman M.; Sarekenova, Karlygash (International Journal of Psychosocial Rehabilitation, 2020)
This article examines the syncretism of the public mythological consciousness of the ancient era. The main properties of this phenomenon are analyzed: syncretism, syncreta, essential anthropomorphism. Examples from the texts of the Old Testament, syncretes of the Ancient Turkic, Middle Greek and Old Russian languages are attracted. It turns out that the Old Testament syncretes are a creative borrowing from the Sumerian language: this is evidenced by examples from the Sumerian written culture. It is determined that during the transition from the appropriating type of economy to the producing type, a process of reflection and criticality arise, which leads to the annihilation of mythological consciousness, the result of which is the emergence of the initial forms of science. The works of outstanding scientists concerning the problems of mythological consciousness, both of the West and the East, were analyzed with the aim of determining the goals and objectives of the study we undertook. In the study of empirical material, we used the methods and techniques of diachronic linguistics, and the methods of cognitive description of ancient and medieval texts to determine the semantics of linguistic units (syncretes that turned into “frozen metaphors”). In addition, syncretes, excerpted from ancient and medieval texts, demonstrate that they were a consequence of syncretism and anthropomorphism phenomenon of the mythological consciousness of ancient times. These syncretes became part of the modern languages’ vocabulary and are preserved in functioning languages after the annihilation of public mythological consciousness.